Synthesis, structure and thermolysis of Ba(II)–M(II) (M = Co, Zn) bimetallic 3D-polymers as precursors of complex oxides. (17th February 2015) - Ryumin, Mikhail A.; Dobrokhotova, Zhanna V.; Emelina, Anna L.; Bukov, Mikhail A.; Gogoleva, Natalya V.; Gavrichev, Konstantin S.; Zorina-Tikhonova, Ekaterina N.; Demina, Liudmila I.; Kiskin, Mikhail A.; Sidorov, Aleksey A.; Eremenko, Igor L.; Novotortsev, Vladimir M.
Graphical abstract: The novel 3D-polymers [BaM(H2 O)5 (Me2 mal)2 ] n (Me2 mal 2− – dimethylmalonic acid dianion) containing M (M = Co 2+, Zn 2+ ) and Ba in a 1:1 ratio were synthesized and characterized by X-ray analysis and a thermal study. It was established that crystalline BaCoO3− x and BaZnO2 were formed as the result of the solid state thermolysis of the porous 3D-polymers. Abstract: The Ba–Co and Ba–Zn heterometallic 3D-polymers [BaM(H2 O)5 (Me2 mal)2 ] n, where Me2 mal 2− is the dimethylmalonic acid dianion, M II  = Co (1 ), Zn (2 ), were synthesized by the reactions of CoSO4 or Zn(OAc)2, respectively, with Ba(OH)2 in water. The thermal dehydration of1 and2 occurs in one step. A kinetic model for the dehydration of complexes1 and2 is proposed. Crystalline BaCoO3− x and BaZnO2 were formed as a result of solid state thermolysis of1 and2 under the following conditions: air flow rate 60 ml/min, heating rate 10 °C/min up to t  = 800 °C (1 ) or 750 °C (2 ), followed by storage for 12 h at the same temperatures.